Effectiveness Of Question Student Have (QSH) Active Learning Model On Learning Outcomes In History Lesson - Setyani, Ita Dwi; Nirmala Putri, Rully Puji; Triyanto, Jefri Rieski; Soepeno, Bambang; Prasetyo, Guruh; Budiman Nasution, Ahmad Arif (JURNAL HISTORICA, 2024)
This research is experimental research, experimental research aims to see whether there is a cause and effect relationship between variables. The conditions used during experimental research are that there must be a control class, manipulation of independent variables, and observation. In this research, several stages were carried out, namely the preparation stage, planning stage, implementation stage and evaluation stage. The tool used to analyze the data in this research is SPSS 26 for window software. because from hypothesis testing it is known that there are differences in learning outcomes in the experimental class which was given the QSH model and the control class which was not given the QSH model in class XI SMA Negeri 1 Kencong with results in F (0.079), sig (0.780), and Partial Eta Squared ( 0.001). The effectiveness of the treatment given on student learning outcomes is known from the sig measurement. The result obtained was 0.780. Based on the criteria listed in the table, the effectiveness of the Question Student Have (QSH) model on class XI learning outcomes is included in the high category. So it can be concluded that the Question Student Have (QSH) model is more effectively used to improve learning outcomes in class XI history subjects in colonialism subjects.